EFEKTIVITAS PENYELESAIAN SENGKETA OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) JAKARTA MELALUI PROSES KONSILIASI - Shinta Dwi Enggraini (2022)
The Consumer Dispute Settlement Agency (BPSK) is an institution at level II regions and is tasked with resolving consumer disputes out of court. In Jakarta, BPSK has been established in North Jakarta. The consumer dispute resolution process at BPSK Jakarta has 3 settlement processes, namely arbitration, mediation and conciliation. However, of the three settlements, conciliation has the least number of choices that consumers choose to resolve their disputes. This paper discusses how the dispute resolution process through the conciliation process and the effectiveness of the conciliation process for consumer dispute resolution. The main problem is answered by empirical legal research methods which include direct observation to BPSK Jakarta and also interviews. Then it resulted in the conclusion that the conciliation process began with a complaint, a pretrial was held and only then was a trial carried out to read out the decision. Conciliation is considered less effective for consumer dispute resolution because the role of the conciliator is passive so it is not allowed to provide advice, direction and instructions which makes it difficult to obtain a decision. Keywords: BPSK, Conciliation, Effectiveness.